Acceptance of ICT in agricultural sector in the Republic of North Macedonia - Paunovski, Ivo (Mednarodno inovativno poslovanje, 2019)
The agricultural industry is very important part of each economy. The main driver of global demand for agricultural products over the next decade will be increasing of population. The fact that the agriculture has to meet the growing needs of food production makes this sector very essential. However, intensifying of food production is more difficult nowadays because of the great impact of climate change, water scarcity and enlarging of land deficiency. The urgent need for increased farm production on less land with less water through further intensification is, therefore, very important. The research related to the acceptance of ICT in Agricultural Sector in Macedonia was done using literature review and semi structured interviews.
Keywords: agriculture; ICT; IKT; kmetijstvo; North Macedonia; Severna Makedonija